Optimization of ASKADIMEGA Method in Extracurricular Recitation of the Qur'an - Anaya, Alvi; Rizka Harfiani; Juli Maini Sitepu (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This extracurricular recitation of the Qur'an was held at Muhammadiyah 7 Junior High School Medan because students had difficulty in reading the Qur'an, so the school took the initiative to hold a Qur'an recitation program. The school thinks that using the rhythm of songs in reading the Qur'an can make it easier for students to understand the Qur'an and the reading becomes more beautiful. In this research on Qur'an recitation, there is the ASKADIMEGA method (What, Who, When, Where, Why, and BaGAimana). This study aims to find out the optimization of the ASKADIMEGA method, the obstacles and solutions faced, as well as evaluation. The informants in this study are the vice principal, extracurricular teachers of Qur'an recitation, students who participate in extracurricular recitation of the Qur'an, the school environment, and things that support the research. This study uses qualitative methods, data collection using observation, interviews, and documentation, and data analysis using Miles and Huberman. The results of this study can be concluded that there are 75% of students who are good and correct in reading the Qur'an and can even sing it according to the predetermined rhythm, and have given birth to a generation of qori and qori'ah who have won competitions at the junior high school level.